Inhibition of Ebola Virus by a Molecularly Engineered Banana Lectin. - Evelyn M Covés-Datson; Julie Dyall; Lisa Evans DeWald; Steven R King; Derek Dube; Maureen Legendre; Elizabeth Nelson; Kelly C Drews; Robin Gross; Dawn M Gerhardt; Lisa Torzewski; Elena Postnikova; et al. (Public Library of Science (PLoS), 2019)
Ebolaviruses cause an often rapidly fatal syndrome known as Ebola virus disease (EVD), with average case fatality rates of ~50%. There is no licensed vaccine or treatment for EVD, underscoring the urgent need to develop new anti-ebolavirus agents, especially in the face of an ongoing outbreak in the Democratic Republic of the Congo and the largest ever outbreak in Western Africa in 2013-2016. Lectins have been investigated as potential antiviral agents as they bind glycans present on viral surface glycoproteins, but clinical use of them has been slowed by concerns regarding their mitogenicity, i.e. ability to cause immune cell proliferation. We previously engineered a banana lectin (BanLec), a carbohydrate-binding protein, such that it retained antiviral activity but lost mitogenicity by mutating a single amino acid, yielding H84T BanLec (H84T). H84T shows activity against viruses containing high-mannose N-glycans, including influenza A and B, HIV-1 and -2, and hepatitis C virus. Since ebolavirus surface glycoproteins also contain many high-mannose N-glycans, we assessed whether H84T could inhibit ebolavirus replication. H84T inhibited Ebola virus (EBOV) replication in cell cultures. In cells, H84T inhibited both virus-like particle (VLP) entry and transcription/replication of the EBOV mini-genome at high micromolar concentrations, while inhibiting infection by transcription- and replication-competent VLPs, which measures the full viral life cycle, in the low micromolar range. H84T did not inhibit assembly, budding, or release of VLPs. These findings suggest that H84T may exert its anti-ebolavirus effect(s) by blocking both entry and transcription/replication. In a mouse model, H84T partially (maximally, ~50-80%) protected mice from an otherwise lethal mouse-adapted EBOV infection. Interestingly, a single dose of H84T pre-exposure to EBOV protected ~80% of mice. Thus, H84T shows promise as a new anti-ebolavirus agent with potential to be used in combination with vaccination or other agents in a prophylactic or therapeutic regimen.